Genetic analysis using Griffing’s approach for forage yield and components in sorghum - C. R. Chudasama1, R. A. Gami2*, R. N. Patel3 and M. A. Patel1 (Electronic Journal of Plant Breeding, 2022)
The present study was carried out using seven parental lines including check CSV 46F and their 21 diallel crosses, excluding reciprocal. The experiment was evaluated in randomised block design with three replications during Kharif 2021 at the Centre for Millets Research, Sardarkrushinagar Dantiwada Agricultural University, Deesa. The analysis of variance (mean sum of squares) revealed significant differences for the genotypes, parents, hybrids and parents vs. hybrids among most of the characters, which explained a sufficient amount of heterosis and was reflected in crosses for fodder yield and its attributing characters. The parents SH 1488 and DS 200 recorded maximum mean performance for green forage yield and dry fodder yield per plant. The result of ANOVA for combining ability revealed that the mean sum of squares due to GCA and SCA were found highly significant for studied characters. The ratio (σ2 GCA/ σ2 SCA) of variances for various characters bare standing of non-additive gene action type in the appearance of forage yield and supporting characters. The parent CSV 21F was found to be a good general combiner for green fodder yield per plant. While, parents SH 1488, DS 200 and CSV 21F were found to be good general combiners for dry fodder yield. The parent SSG 59-3 was a very good general combiner for days to flowering, total plant height, stem diameter, crude protein and HCN content. The crosses S 652 × CSV 46F, DS 200 × CSV 21F and SSG 59-3 × S 652 for green fodder yield per plant, while SSG 59-3 × S 652, DS 200 × CSV 21F and SSG 59-3 × CSV 46F for dry fodder yield per plant recorded the highest sca effects. Based on all the genetic parameters, the crosses SSG 59-3 × S 652, SH 1488 × S 652, SH 1488 × DSF 182 and DS 200 × CSV 21F with high mean performance, high sca effects and at least one parent having good to moderate gca effects would increase the frequency of favourable alleles. Therefore, it may be hopeful to select good homozygous lines to ameliorate respective characters in forage sorghum. It can also be used directly in varietal breeding programmes.